Evaluation of Debt Payment Procedures through Domestic Documentary Credit (SKBDN): A Case Study of PT Varia Usaha Beton - Viona Adelia Safitri; Vicky Vendy (Universitas Muhammadiyah Makassar, 2025)
This study investigates the implementation of vendor debt payment procedures through Domestic Documented Credit Letters (SKBDN) at PT Varia Usaha Beton Sidoarjo. The purpose is to evaluate the effectiveness, efficiency, and challenges of SKBDN in supporting corporate payment systems. Data collection methods included observation, documentation, and semi-structured interviews with key personnel from the Treasurer Division. The findings show that SKBDN follows a structured process, beginning with document preparation, internal verification, managerial approval, and subsequent submission to the bank. This system provides a strong payment guarantee and strengthens internal financial control. However, its practical application remains less effective because fund disbursement requires up to six months, leading to delays in vendor transactions. The delays are primarily caused by document complexity, multi-level verification, and extended coordination between parties. Despite these drawbacks, SKBDN offers financial advantages since administrative costs and penalties are shifted to vendors, creating cost efficiency for the company. As a response to prolonged payment timelines, PT Varia Usaha Beton has considered adopting Supply Chain Financing (SCF), even though it involves higher costs. This study provides valuable insights for organizations evaluating debt payment systems, highlighting the importance of balancing timeliness, cost efficiency, and operational effectiveness.